Effect of pyrolysis on oil shale using superheated steam: A case study on the Fushun oil shale, China. (1st October 2019) - Wang, Lei; Zhao, Yangsheng; Yang, Dong; Kang, Zhiqin; Zhao, Jing
Highlights: Internal structure of oil shale pyrolysis with injection steam under in situ condition was studied. Porosity of oil shale along bedding planes is 12.77 times that of natural oil shale. Internal fractures of pyrolytic oil shale were mainly dominated by microcracks. The proportion of pyrolytic orebody with permeability ranging from 1.8 × 10 −3 nm 2 to 3.0 × 10 −3 nm 2 was 63.51%. Oil shale is transformed from dense rock to porous medium under the effect of superheated steam. Abstract: In the in situ pyrolysis of oil shale (OS) with superheated steam (SS), the internal pores and fractures of the OS act as channels for the migration of steam and locations for heat exchange. After a laboratory test of the in situ pyrolysis of OS with SS, 30 OS samples located in different zones between the injection and production wells were collected. The main parameters of pore and fracture structures inside OS samples were investigated. The results first showed that in each position along the bedding planes, the effective porosity was greater than 19.41%. The internal OS fractures were mainly dominated by microfractures, with lengths between 100 µm and 500 µm. The average pore diameter of the orebody was between 52.77 nm and 69.01 nm, and the aperture of the microfractures was between 59.31 µm and 68.85 µm. Then, in the position near the roof bedrock perpendicular to the bedding directions (BD), the effective porosity and pore diameter of the orebody were small. Only a few cracks were observed in the rock mass, and the distribution of the pore groups in the 3D space was fragmented and had poor connectivity. Finally, in the whole studied OS orebody, the proportion of ore layers with permeabilities ranging from 1.8 × 10 −17 m 2 to 3.0 × 10 −17 m 2 was 63.51%, which proved that the connectivity of the pores and fractures in the large area was superior to other areas.